2001
DOI: 10.1046/j.1365-2648.2001.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

You can do it if you set your mind to it: a qualitative study of patients with coronary artery disease

Abstract: Patients may comply well with follow-up visits but less with lifestyle changes. By identifying different 'characteristics', 'prerequisites' and 'difficulties' that describe patients' compliance, it should be possible to make treatment more individual. Nurses have a significant role in supporting these patients since they are more accessible than physicians. Nurses also have a responsibility to work together with patients to empower them, in order to make their lifestyle changes and self-care activities managea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 21 publications
7
55
0
Order By: Relevance
“…74 Other studies have reported patient concerns about medicines without relating this to compliance. This includes concern about side effects, 81,[84][85][86][87] as well as patients perceiving medicines to be an "intrusion on their daily life" and concern about having to take them for the rest of their lives 84 or that some patients disliked taking medicines. 83,84,87 Studies have reported that some patients view medicines in terms of preventing another heart attack, 74,82,84 delaying progression of CVD, 88 or as an aid to recovery.…”
Section: Patient Perspectives On Taking Prescribed Medicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…74 Other studies have reported patient concerns about medicines without relating this to compliance. This includes concern about side effects, 81,[84][85][86][87] as well as patients perceiving medicines to be an "intrusion on their daily life" and concern about having to take them for the rest of their lives 84 or that some patients disliked taking medicines. 83,84,87 Studies have reported that some patients view medicines in terms of preventing another heart attack, 74,82,84 delaying progression of CVD, 88 or as an aid to recovery.…”
Section: Patient Perspectives On Taking Prescribed Medicinesmentioning
confidence: 99%
“…83,84,87 Studies have reported that some patients view medicines in terms of preventing another heart attack, 74,82,84 delaying progression of CVD, 88 or as an aid to recovery. 85 However, studies have also found that either some or many patients did not know what medicines they were taking or how the medicines work. 76 …”
Section: Patient Perspectives On Taking Prescribed Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting factors reported by the patients recovering after MI and coronary artery disease include both personal factors and external support [2,[9][10][11][12][13][14][15] . Besides good physical health, various psychological factors have been reported to be supportive after MI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a variety of personal coping strategies have been reported [11][12][13][14][15] . Supporting external factors include helpful interpersonal relations and concrete practical help from family, friends and professionals [2,9,11,16] .…”
Section: Introductionmentioning
confidence: 99%